D2SA a DPSK-based distributed sample acquisition for coherently demodulated MPSK - Byoung-Hoon Kim (IEEE Transactions on communications)
We present DPSK-based distributed sample acquisition (D2SA) as a novel variant of the distributed sample acquisition family for application to the M-ary phase-shift keying signaling direct-sequence code-division multiple-access systems. The D 2SA employs differentially coherent phase-shift keying (DPSK) to convey the shift register generator state samples and the prerotation of the data constellation to realize the coherent demodulation of the data stream. The use of DPSK instead of orthogonal modulation as the means of the state sample conveyance improves the system performance in terms of both system complexity and acquisition time